El ajuste estructural y los campesinos - Gonzales de Olarte, Efraín (Colección Mínima ;, 1996)
"This little volume looks at the result of market-oriented macroeconomic policies on the peasantry. The impact of the stabilization policies of the 1980s-early 1990s are examined through a case study in the highlands of Cajamarca. The structural adjustment programs of the 1990s are studied in four regions of the highlands and the coast. A balanced examination reveals that both negative and positive effects are experienced by the peasantry, and that State policy should be an investment in human capital through education, health services, and infrastructural services"--Handbook of Latin American Studies, v. 57.